Study of serum lipid profile: An observation between criminality and psychosis in relation to aggression - Bhakta Bandhu Das; Ajay Mishra; Asitkumar Sethi; Sarada Prasanna Swain (International Journal of Health and Clinical Research, 2022)
Background & aim: Aggressive and violent behavior is being increasingly viewed as a public health problem and violence prevention has become one of the most pressing issues facing our society today. Our aim was to find correlation between lipid profile, criminal behavior and psychosis. Method: The present study involved 120 participants consisted of four groups. Each group consisted of 30 subjects. This study was done in two different places. One is at Circle jail Choudwar, Cuttack and second place is at in-patient Department of Psychiatry MHI, S.C.B medical college, Cuttack. First study group was male convicted prisoners selected at Circle Iail Choudwar having no psychiatric illness .The control group for this was selected from general population. The second study group was male psychotic patients having criminal record. The control group for this was selected from same ward, of male psychotic patient having no criminal record. The objective was to study the serum lipid profile of each group and it's relationship in criminality, psychosis and aggression. All the subjects in first study group and its controls were screened with General Health Questionnaire (GHQ-12).All the subjects in second study group and its controls were assessed with Overt Aggression Scale (OAS) for scoring of aggression and Brief Psychiatry Rating Scale (BPRS). Results: The criminal group without psychiatric illness showed significantly lower cholesterol (p=0.010) than general population and also lower than the psychotic in-patients without history of crime. The psychotic in-patient group with criminal records showed significantly lower cholesterol (p=0.001) than psychotic patients of no criminal record and also lower than non-psychotic criminal offenders. The psychotic criminal offenders showed lowest mean cholesterol than all other three groups. Conclusion: Our study proves a causal connection between low cholesterol and behavioral problem arising out of criminality, psychotic aggression.